Help-seeking behavior and self-medication of a population in an urban area in turkey: Cross sectional study - (:unkn) unknown (PABST SCIENCE PUBLISHERS, 2000)
Aim. To define help-seeking behavior and self-medication among people with different symptoms and complaints in an industrialized urban area of Turkey. Methods. This cross-sectional study was carried out in the city center of Kocaeli province, Western Turkey, in October-November 1998. To research help-seeking behavior in respect of secondary prevention and curative practices, we randomly selected households (N=812), interviewed the household members at their home, and recorded the reasons for visiting a pharmacy in 6 pharmacies (N=1,331 visits to pharmacy) in the Kocaeli region. Results. The majority of the interviewed knew the meaning and importance of regular medical checkups, and only 7% had never underwent periodic checkups, mainly because of lack of interest or time. Self-medication was found to be the dominant mode of help-seeking behavior, especially in the case of pain. The proportion of unprescribed to prescribed drugs was 1:1.75, with analgetics, antipyretics, expectorants and antitussives as the most commonly requested unprescribed drugs. Conclusion. A considerable amount of health care occured within the popular sector, with self-medication and pharmacist's advice as dominant modes of behavior. The health care system should take this in account when planning activities aimed at detection of disease.
Keywords: helping behavior; life style; medically underserved area; medicine; traditional; prescriptions; drug; public health; social behavior; Turkey; OVER-THE-COUNTER; ILLNESS; DRUGS; HEALTH; CARE